The Tailored CFD Package ‘containmentFOAM’ for Analysis of Containment Atmosphere Mixing, H2/CO Mitigation and Aerosol Transport - Stephan Kelm; Manohar Kampili; Xiongguo Liu; Allen George; Daniel Schumacher; Claudia Druska; Stephan Struth; Astrid Kuhr; Lucian Ramacher; Hans-Josef Allelein; K. Arul Prakash; G. Vijaya Kumar; et al. (Fluids, 2021)
The severe reactor accident at Fukushima Daiichi Nuclear Power Plant (2011) has confirmed the need to understand the flow and transport processes of steam and combustible gases inside the containment and connected buildings. Over several years, Computational Fluid Dynamics (CFD) models, mostly based on proprietary solvers, have been developed to provide highly resolved insights; supporting the assessment of effectiveness of safety measures and possible combustion loads challenging the containment integrity. This paper summarizes the design and implementation of containmentFOAM, a tailored solver and model library based on OpenFOAM®. It is developed in support of Research & Development related to containment flows, mixing processes, pressurization, and assessment of passive safety systems. Based on preliminary separate-effect verification and validation results, an application oriented integral validation case is presented on the basis of an experiment on gas mixing and H2 mitigation by means of passive auto-catalytic recombiners in the THAI facility (Becker Technologies, Eschborn, Germany). The simulation results compare well with the experimental data and demonstrate the general applicability of containmentFOAM for technical scale analysis. Concluding the paper, the strategy for dissemination of the code and measures implemented to minimize potential user errors are outlined.